PERAN FINANCIAL TECHNOLOGY SISTIM PEER TO PEER LENDING ( P2P) SEBAGAI SALAH SATU BENTUK ALTERNATIF SUMBER PENDANAAN UMKM - murifal, Badar (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2018)
Fintech is a portmanteau of financial technology that describes an emerging financial services sector in the 21st century. Originally, the term applied to technology applied to the back-end of established consumer and trade financial institutions. Since the end of the first decade of the 21st century, the term has expanded to include any technological innovation in the financial sector, including innovations in financial literacy and education, retail banking, investment and even crypto-currencies like bitcoin. The term financial technology can apply to any innovation in how people transact business, from the invention of digital money to double-entry bookkeeping. Since the internet revolution and the mobile internet revolution, however, financial technology has grown explosively, and fintech, which originally referred to computer technology applied to the back office of banks or trading firms, now describes a broad variety of technological interventions into personal and commercial finance. As one of a variety of business type in Indonesia , UMKM ( Usaha Mikro, Kecil dan Menengah) as an Indonesian Micro Small and Medium Enterprises (MSMEs) can take involve to overcome their weakness of capital and financing . They can growth well  without any obstacles how to find the loan not only from the banks but also it comes also from the other party such like financial technology concept as an alternatives for financing with easily procedures, no collateral  and not taking time. At the last, three parties who involved in financial technology such as Investor ,  financial technologi provider and small business enterprises or Usaha Mikro, Kecil dan Menengah can make some advantageuos for their business growing.